Influence of implant properties and local delivery systems on the outcome in operative fracture care. Issue 3 (March 2016) - Metsemakers, W-J.; Moriarty, T.F.; Nijs, S.; Pape, H.C.; Richards, R.G.
Abstract: Fracture fixation devices are implanted into a growing number of patients each year. This may be attributed to an increase in the popularity of operative fracture care and the development of ever more sophisticated implants, which may be used in even the most difficult clinical cases. Furthermore, as the general population ages, fragility fractures become more frequent. With the increase in number of surgical interventions, the absolute number of complications of these surgical treatments will inevitably rise. Implant-related infection and compromised fracture healing remain the most challenging and prevalent complications in operative fracture care. Any strategy that can help to reduce these complications will not only lead to a faster and more complete resumption of activities, but will also help to reduce the socio-economic impact. In this review we describe the influence of implant design and material choice on complication rates in trauma patients. Furthermore, we discuss the importance of local delivery systems, such as implant coatings and bone cement, and how these systems may have an impact on the prevalence, prevention and treatment outcome of these complications.